2011
DOI: 10.1016/s2255-4971(15)30205-6
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of the Tibial Component in Total Knee Arthroplasty: Report on Two Cases

Abstract: The authors report the rare occurrence of two cases of fracture of the tibial component in total knee arthroplasty. They review the literature and discuss the main factors that can cause failure of the implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…3 This number has increased slightly but remains a rare finding with few cases being described since that time frame, and even less so with a contemporary component. [4][5][6][7][8] This case report represents, to our knowledge, the first case report of a Zimmer® NexGen® tibia tray fracture, 77months from the index operation.…”
Section: Introductionmentioning
confidence: 78%
“…3 This number has increased slightly but remains a rare finding with few cases being described since that time frame, and even less so with a contemporary component. [4][5][6][7][8] This case report represents, to our knowledge, the first case report of a Zimmer® NexGen® tibia tray fracture, 77months from the index operation.…”
Section: Introductionmentioning
confidence: 78%
“…Incorrectly aligned components, varus malalignment, and ligament imbalance have been associated with possible factors that lead to tibial component failure [ 4 , 12 , 13 , 16 , 20 ]. Gilg et al [ 3 ] and Abernethy et al [ 4 ] suggested that a failure to correct varus deformity following TKA can lead to displacement of the mechanical axis to the medial side and subsequent fracture.…”
Section: Discussionmentioning
confidence: 99%
“…One patient gained significantly more weight in the time leading to his revision, increasing from a BMI of 32.85 to 36.4. Previous studies have mentioned how the asymmetrical forces associated with obesity and soft-tissue imbalance could compromise implant life span and lead to fracture [ 17 , 20 ]. Bagsby et al [ 22 ] reported cementless fixation using the Stryker Triathlon Tritanium design performed better than cemented fixation in patients who are morbidly obese with regards to revision rate and long-term survivorship.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,9,19,28 Common modes of failure in modern total knee arthroplasty are aseptic loosening, instability, infection, polyethylene wear, and malalignment. 11 Severe varus malalignment 29 and high BMI 28 are postulated to be causative in the few reports of recent tibial component fracture. Regardless, failed arthroplasty in less than 5 years is dismal.…”
Section: Discussionmentioning
confidence: 99%
“…Varus alignment has been implicated as a mechanism of tibial component fracture. 29 Signature guidance has been reported by some authors to improve alignment of knee components but is not without controversy. 15,[30][31][32][33][34][35][36] We did not have long leg films or computed tomography scans and recognize there is concern in assessment of alignment with standard knee films.…”
Section: Discussionmentioning
confidence: 99%